2x(x+1)=7

Simple and best practice solution for 2x(x+1)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+1)=7 equation:


Simplifying
2x(x + 1) = 7

Reorder the terms:
2x(1 + x) = 7
(1 * 2x + x * 2x) = 7
(2x + 2x2) = 7

Solving
2x + 2x2 = 7

Solving for variable 'x'.

Reorder the terms:
-7 + 2x + 2x2 = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + 2x + 2x2 = 0

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
-3.5 + x + x2 = 0

Move the constant term to the right:

Add '3.5' to each side of the equation.
-3.5 + x + 3.5 + x2 = 0 + 3.5

Reorder the terms:
-3.5 + 3.5 + x + x2 = 0 + 3.5

Combine like terms: -3.5 + 3.5 = 0.0
0.0 + x + x2 = 0 + 3.5
x + x2 = 0 + 3.5

Combine like terms: 0 + 3.5 = 3.5
x + x2 = 3.5

The x term is x.  Take half its coefficient (0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
 + 0.25 + x2 = 3.5 + 0.25

Combine like terms:  + 0.25 = 1.25
1.25 + x2 = 3.5 + 0.25

Combine like terms: 3.5 + 0.25 = 3.75
1.25 + x2 = 3.75

Factor a perfect square on the left side:
(x + 0.5)(x + 0.5) = 3.75

Calculate the square root of the right side: 1.936491673

Break this problem into two subproblems by setting 
(x + 0.5) equal to 1.936491673 and -1.936491673.

Subproblem 1

x + 0.5 = 1.936491673 Simplifying x + 0.5 = 1.936491673 Reorder the terms: 0.5 + x = 1.936491673 Solving 0.5 + x = 1.936491673 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 1.936491673 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 1.936491673 + -0.5 x = 1.936491673 + -0.5 Combine like terms: 1.936491673 + -0.5 = 1.436491673 x = 1.436491673 Simplifying x = 1.436491673

Subproblem 2

x + 0.5 = -1.936491673 Simplifying x + 0.5 = -1.936491673 Reorder the terms: 0.5 + x = -1.936491673 Solving 0.5 + x = -1.936491673 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -1.936491673 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -1.936491673 + -0.5 x = -1.936491673 + -0.5 Combine like terms: -1.936491673 + -0.5 = -2.436491673 x = -2.436491673 Simplifying x = -2.436491673

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.436491673, -2.436491673}

See similar equations:

| 8p-1+p=10p-9 | | 2z-3=53+9z | | 4+3y=-12 | | -17=4x+12-9x | | 3x-5/x-1=3x-2/x+2 | | -0.4p=0.2p+9 | | -7x+1=6 | | 8/3-2 | | 7f-8=2 | | 2x5/2+5x3/2=7x1/2 | | 7/12+1/4 | | 13/85.8 | | -c+4=-2c | | x/2+5=-12 | | -8x-2=24-9x | | 45/34a=23.3+46a | | 5.6q-3.4-4.9q=0.3q-2.3 | | 3-3(3n-3)=39 | | 3a+9b+-5a+15b= | | 5/9=h/30 | | -8x-2=24-9 | | 8+16p^2=33 | | 85.5/13 | | 9x-4=5x+4 | | 4t+5=-10+t | | v-15=9 | | 63(x-3)=9(x+3) | | 2(x+4)=3x+5 | | 7a+-9b+3a+9b= | | 5x+9=-3 | | O(5)=2(5)-1 | | 8m-7=21+m |

Equations solver categories